South Cina Sea Maritime Security - Dadang Sobar Wirasuta (The Republic of Indonesia Defense University, 2015)
Conflict South China Sea is a new road for obtaining natural resource, where some countries have conflicting claim over the Spratly Archipelago and Paracell. Indonesian Navy as a component of national strength participates in the application of national strategy into naval strategy and operationalizing in the diplomacy and multilateral exercises to enhance interoperability among navies in South China Sea region. Regional Maritime partnership is smart choice when regional stability is becoming the goal of all states to maintain regional security in South ChinaSea, Indonesian Navy need strong powerfull fleet for readiness, sea control and “world class navy” for peace in south China Sea